2020
DOI: 10.21203/rs.3.rs-104804/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of the tryptophan-nicotinamide pathway in a model of severe malnutrition induced liver dysfunction

Abstract: Mortality in children with severe malnutrition is strongly related to signs of metabolic dysfunction, such as hypoglycemia. Lower circulating tryptophan levels in children with severe malnutrition suggest a possible disturbance in the tryptophan-nicotinamide (TRP-NAM) pathway and subsequently NAD+ dependent metabolism regulator sirtuin1 (SIRT1). We report that severe malnutrition in weanling mice, induced by feeding a low protein diet, leads to an impaired TRP-NAM pathway and affects hepatic mitochondrial turn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…It is well known that severe acute malnutrition affects glucose homeostasis in infants (4,36), a feature that persists later in life (37,38). Furthermore, studies in rodents have shown that post-weaning PEM induces hepatic alterations, such as steatosis and impaired hepatic mitochondrial turnover (39)(40)(41). Interestingly, two independent studies using a high-fat diet (58% kcal from fat) after LPD have shown that PEM after weaning does not potentiate fat accumulation, hepatic steatosis and insulin resistance in adult young mice (39,42).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that severe acute malnutrition affects glucose homeostasis in infants (4,36), a feature that persists later in life (37,38). Furthermore, studies in rodents have shown that post-weaning PEM induces hepatic alterations, such as steatosis and impaired hepatic mitochondrial turnover (39)(40)(41). Interestingly, two independent studies using a high-fat diet (58% kcal from fat) after LPD have shown that PEM after weaning does not potentiate fat accumulation, hepatic steatosis and insulin resistance in adult young mice (39,42).…”
Section: Discussionmentioning
confidence: 99%
“…It is however worth noting that liver steatosis is not a common observation among children with congenital intestinal lymphangiectasia, a disease associated with lymphatic damage 56 . Hepatic lipid accumulation in animal models of SM has so far been proposed to be related to mitochondrial dysfunction, peroxisomal damage 57, 58 or choline deficiency 59 . However, in these animal studies, rodents were fed low-protein diets which did not induce oedema.…”
Section: Discussionmentioning
confidence: 99%